2000
DOI: 10.1037/0278-6133.19.5.411
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and psychological predictors of changes in dietary fat consumption in adults with high blood cholesterol following counseling in primary care.

Abstract: The associations between sociodemographic variables, psychological factors, and changes in dietary fat consumption over 4 months were assessed in a randomized controlled trial of behavioral counseling versus standard advice. Patients were 141 men and 150 women, with an average age of 52.1 years and total cholesterol level of 7.27 mmol/l (278 mg/dl). Smokers, younger patients, and those with greater body mass index had higher fat intake at baseline. Behavioral counseling led to greater reductions in fat intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
(55 reference statements)
1
31
1
Order By: Relevance
“…The brief measures of self-efficacy used previously (e.g. Annesi, 2007; Steptoe et al, 2000; Van Duyn et al, 2001), however, have little or no supporting evidence of construct validity. Tests of factorial validity have been reserved for surveys with greater numbers of items (i.e.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The brief measures of self-efficacy used previously (e.g. Annesi, 2007; Steptoe et al, 2000; Van Duyn et al, 2001), however, have little or no supporting evidence of construct validity. Tests of factorial validity have been reserved for surveys with greater numbers of items (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…Significant positive effects of self-efficacy have been reported for weight-loss (Byrne et al, 2012; Hays et al, 2014; Palmeira et al, 2007; Shin et al, 2011; Warziski et al, 2008), physical activity (Linde et al, 2006; McAuley & Blissmer, 2000), and healthful eating (Hagler, 2007; Henry, Reimer, Smith, & Reicks, 2006; Steptoe, Doherty, Kerry, Rink, & Hilton, 2000; Stotland & Zuroff, 1991). Other studies, however, have not found these relationships (Annesi, 2007; Linde et al, 2004; Teixeira et al, 2002; Teixeira et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrated that fat intake was associated with lower self-efficacy and that self-efficacy is a better predictor of weight loss than other psychological parameters (Steptoe, Doherty, Kerry, Rink, & Hilton, 2000;Wamsteker et al, 2005). Selfefficacy is also closely related to goal setting.…”
mentioning
confidence: 99%
“…A study using nurses to provide brief behavioral counseling produced significant decreases in dietary fat intake in a randomized test in individuals with coronary risk factors (104). Other studies have found similar changes (70,103).…”
Section: Individual Randomized Trialsmentioning
confidence: 91%